Thyroid Dysfunction in Patient with Cirrhotic Liver Disease and its Relation to the Severity of Cirrhosis - Asif Islam, Rana Zohaib Munawar, Muhammad Habib, Zainab Younus, Mohammad Omar Yousofzai, Mohammad Khalid Hamidi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Liver carries its vital significance due to ability to control over excretion, metabolism and transportation of the thyroid hormone. Peripheral change of T4 to T3 occurs in the live leading to initiation of action and breakdown of the hormones. Any morbidity in the liver can result in the decrease in TSH level and leading to thyroid dysfunction. So it is necessary to determine this impact in cases with liver cirrhosis. Methodology: 115 cases of chronic liver disease who were not on the any therapy were involved in this research. The age of >18 years and both genders were selected. Data was collected from Department of Medicine, Lahore General Hospital, and Lahore in a duration of one year. All the demographics and baseline information mandatory for the selection of the appropriate sample was recorded. The participants were informed about the purpose of the research and after their consent they were selected for this study. Finally, the collected data was analyzed using SPSS 23.inc. Practical implication: Thyroid dysfunction in patients with cirrhotic liver disease has practical implications for their management and outcomes. Regular screening and early intervention are important to detect and treat thyroid dysfunction promptly. Managing both cirrhosis and thyroid dysfunction requires a multidisciplinary approach involving hepatologists and endocrinologists. Patient education and support are crucial for raising awareness and ensuring adherence to treatment plans. Further research is needed to understand the relationship between thyroid dysfunction and cirrhosis severity and to explore potential therapeutic targets. Integrating thyroid evaluation into the overall management of cirrhosis can improve patient outcomes and quality of life. Results: Mean age of 51(9.81) years were involved in this research. The male cases were higher in number 81(70.4%). The body mass index value was 27.5(3.65). Child Pugh A class was noted in 37(32.2%), B in 32(27.8%) & C in 46(40%). Serum T3 level was 2.05, serum T4 level was 8.69, serum FT3 level was 3.06, serum FT4 was 1.24 and TSH level was having a mean value 3.15. A significant inverse relationship noted in the severity of cirrhosis and thyroid profile levels. Conclusion: Thyroid function depends on the smooth functioning of the liver through its hormones. As the liver compromise some disease, this normal function disturbs and thyroid dysfunction occurs which increase with the harshness of liver disease. Keywords: Liver Disease, Thyroid Dysfunction, HCV, TSH